Un grillo en Times Square - Selden, George, 1929-1989; Williams, Garth; Longshaw, Robin (New York : Square Fish, 2012)
The adventures of a country cricket who unintentionally arrives in New York and is befriended by Tucker Mouse and Harry Cat.
Translation of: The cricket in Times Square.
Keywords: Crickets -- Juvenile fiction; Mice -- Juvenile fiction; Cats -- Juvenile fiction; Grillos -- Novela juvenil; Ratones -- Novela juvenil; Gatos -- Novela juvenil